Automatização de acionamentos por meio de tarefas agendadas usando comunicação por rádio frequência - Langfeldt, Carolina (2013)
This work relates an application development that allows a common user to program a task scheduling to turn on and off equipments and devices in predefined dates and times. The project consists in an integrated group of hardware and software that can perform these functionalities in different environments with different needs. The hardware system is modular, being composed by a central control that connects a computer through an USB port and secondary modules that command their respective loads. Three software codes belong to the solution: the drive module firmware, the central control firmware and the user’s interface application, the latter of which is executed on a computer. Development has as goals not only system correctness but also its economic feasibility as a consumer’s asset. The prototype functionality complied with all requisites, performing the scheduling and the execution of tasks with relative commodity and practicality to the user.